The Long Run - Simon, Adam. (Tufts University. Tisch Library., 2021)
Thesis (M.A.)--Tufts University, 2020.; Submitted to the Dept. of Music.; Advisors: John McDonald, and Kareem Roustom.; Committee: John McDonald, Kareem Roustom, and Michael McLaughlin.; Keyword: Musical composition.; The Long Run is a thirty-minute-long work of concert music in six movements, setting a new poem of Rita Powell. The poem's title refers to long-distance running, which, for the poet, serves as a way to access understanding of life's deeper questions and mysteries. Its movements retell formative moments from Rita's life, which helped sculpt her sense of self, and a sense of the divine. Framed by an "Introit" and "Postlude" the inner four movements bring us through the four seasons, and stories from her own life which led her on her spiritual journey. Despite growing up in a secular background, Rita now serves as the rector for the Harvard Episcopal Chaplaincy where she leads many ecumenical and interfaith programs. The Long Run explores themes of religion, spirituality and personal growth. It is scored for vocal quartet, piano, and string quartet.